2011
DOI: 10.1002/eji.201141693
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus entry into NK cells requires CD16 expression and triggers cytotoxic activity and cytokine secretion

Abstract: Human papillomavirus (HPV) infections account for more than 50% of infection-linked cancers in women worldwide. The immune system controls, at least partially, viral infection and around 90% of HPV-infected women clear the virus within two years. However, it remains unclear which immune cells are implicated in this process and no study has evaluated the direct interaction between HPVs and NK cells, a key player in host resistance to viruses and tumors. We demonstrated an NK-cell infiltration in HPVassociated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 55 publications
3
40
0
Order By: Relevance
“…Interestingly, we have observed that the enhanced synthesis of IFN-␥ observed in vitro upon quadrivalent HPV (type 6/11/16/18) vaccine immunization is not affected by ILT2 engagement, indicating that the regulatory effect of this receptor is not exerted on all immune parameters that are relevant in the response to HPV. In this regard, it has been recently reported that NK cells exposed to HPV VLPs show increased cytotoxic activity and cytokine production (including IFN-␥) (19). Therefore, it is possible that the enhanced production of IFN-␥ observed by us upon HPV immunization could be related to the increased expression of activating receptors by NK cells and to a lack of a regulatory effect mediated by ILT2 on this immune parameter.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, we have observed that the enhanced synthesis of IFN-␥ observed in vitro upon quadrivalent HPV (type 6/11/16/18) vaccine immunization is not affected by ILT2 engagement, indicating that the regulatory effect of this receptor is not exerted on all immune parameters that are relevant in the response to HPV. In this regard, it has been recently reported that NK cells exposed to HPV VLPs show increased cytotoxic activity and cytokine production (including IFN-␥) (19). Therefore, it is possible that the enhanced production of IFN-␥ observed by us upon HPV immunization could be related to the increased expression of activating receptors by NK cells and to a lack of a regulatory effect mediated by ILT2 on this immune parameter.…”
Section: Discussionmentioning
confidence: 81%
“…In most individuals, HPV is cleared within 2 years after infection, but in ~10% of infected people, the virus persists long term, and can cause low-grade intraepithelial squamous lesions that may progress to dysplasia, in situ carcinoma, and finally invasive carcinoma. 69 HPV has developed multiple immune evasion strategies to escape CTL- and NK-cell–mediated control.…”
Section: Evidence For a Role For Nk Cells In Virus-associated Tumentioning
confidence: 99%
“…The authors suggest that NK cells might be activated by HPV viral particles. It has been shown that NK cells are abundantly present in the tissue of preneoplastic cervical lesions but much less cells have been detected in cervical squamous cell carcinomas [15, 16]. In patients with HNSCC, decreased numbers of NK cells in the peripheral blood have been detected independently of the etiology of the tumor [17, 18].…”
Section: Introductionmentioning
confidence: 99%